2013
DOI: 10.1016/j.biopsych.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Randomized Trial for Cocaine Abuse: Disulfiram and Dopamine β-Hydroxylase

Abstract: Background Disulfiram has been an effective cocaine addiction pharmacotherapy, and one of its possible mechanisms of efficacy is through copper chelation and inhibition of an enzyme involved in catecholamine metabolism, dopamine β-hydroxylase (DβH), which converts dopamine to norepinephrine. A variant in the gene encoding DβH leads to reduced DβH activity and as such, disulfiram may not be an effective treatment of cocaine dependence for individuals with this variant. This study explored that potential matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 73 publications
4
111
0
Order By: Relevance
“…Accordingly, in women, the inhibition of DβH activity due to disulfiram administration may be attenuated by the stimulating effect of DβH activity induced by oestrogens and/or oral contraceptives. Another study, not included in the meta-analysis we selected, recently found an inverse relationship between the efficacy of disulfiram and DβH activity in patients with cocaine dependence [86] .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in women, the inhibition of DβH activity due to disulfiram administration may be attenuated by the stimulating effect of DβH activity induced by oestrogens and/or oral contraceptives. Another study, not included in the meta-analysis we selected, recently found an inverse relationship between the efficacy of disulfiram and DβH activity in patients with cocaine dependence [86] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 74 cocaine-and opioid-dependent individuals stabilized on methadone, Kosten et al found that patients with the DbH genotype conferring normal levels of the enzyme responded preferably to disulfiram (reduction in cocaine positive urines from 84 to 56%, p = 0.0001), while those patients with the DbH-genotype conferring low levels of the enzyme did not show a medication effect [95]. Other pharmacogenetic targets examined as potential genotypes by which to identify individuals for whom disulfiram may be effective include ANKK1, DRD2 and ADRA1A [96,97].…”
Section: Disulfirammentioning
confidence: 99%
“…In a follow-up study by Carroll et al (2012), the disulfiram treatment group with no 12-step program support had the highest rate of cocaine use. The results of all of these trials must be interpreted with caution because the latest reports indicate that the ability of disulfiram to reduce cocaine use is dependent on both dose and pharmacogenetic considerations (Haile et al, 2012;Kosten et al, 2013;Shorter et al, 2013). Thus, despite these conflicting outcomes, there does appear to be sufficient evidence to continue the evaluation of DBH inhibitors as cocaine pharmacotherapies.…”
Section: Effects Of Dopamine B-hydroxylase Inhibition In Monkeysmentioning
confidence: 99%